(untitled) (Panacea Journal of Medical Sciences, 2024)
Introduction: Because India has long been a land of exotic snakes, snakebite is a serious occupational and rural hazard. Physicians pay very little attention to this occupational hazard despite the high morbidity and death. Objective: To study the various clinical profiles and the time interval between bite and start of treatment. Materials and Methods: Patients were categorized based on the envenomation centred by patient history and definitive bite evidence and graded (I-IV) grounded on a series of manifestations observed in association with the onset of treatment time that distinguishes a venomous from a non-venomous snake attack. Patients were obligating local inflammation owing to tourniquet use besides local innate therapies. Results: Of the 100 patients deliberated, it was evident that there existed a minimal difference between the bites instigated by the snake type. Higher abnormal clotting was perceived on the arrival of patients (78%). While envenomation was predominantly reported to prompt primary coagulation abnormalities (84.32 %), neurotoxin manifestation was also found to occur at a lower rate (11.76 %). Both symptoms were also observed at a minimal level (3.92 %). Higher rates of renal failure were also reported and the clotting time normalization depended largely on patient admission time post-attack. In this investigation, the time gap between the bite and the commencement of therapy was not associated with the time required to normalize the coagulation abnormalities or develop a complication. Conclusion: The study also proposes appropriate protective and awareness measures that could save humankind and these reptiles together.